EVALUASI ADVOKASI PENYELESAIAN KONFLIK SENGKETA TANAH (Studi Kasus Konflik Sengketa Tanah Petani Toili & PT Kurnia Luwuk Sejati di Kec.Toili Kab.Banggai Propinsi Sulawesi Tengah) - , Andriany Badrah ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis aims to determine the extent to which advocacy is conducted by Front Rakyat Advokasi Sawit (FRAS) for the handling of conflict in Central Sulawesi land disputes between famers Toili and PT Kurnia Luwuk Sejati (PT KLS). The background of this research is about the conflict of land disputes between farming communities Toili with PT KLS in Banggai regency of Central Sulawesi province. Where PT KLS has a palm plantation business and Hutan Tanaman Industri (HTI). This land dispute started after PT Berkat Hutan Pustaka (PT BHP) is wholly owned by PT KLS, the conversion of forests into oil palm plantations. PT BHP is a company engaged in the business of HTI. PT BHP itself is the holder of an area of 13,400 ha HTI license district in the region. Toili and Toili West. PT BHP is a joint venture of PT KLS. Conflict land dispute occurred when PT and PT BHP KLS started doing oil palm plantation activities and has lasted a long time. Mediation for conflict resolution efforts have been made by the Badan Perwakilan Desa (BPD), Banggai regency government and National Human Rights Commission. Mediation efforts have been made yet deliver results as expected by the peasant farmers Toili then have recourse to some non-governmental organizations (NGOs) in Palu is incorporated in the Front Rakyat Advokasi Sawit (FRAS) to provide guidance in an effort to dispute the claimed land as land Toili farming communities. Conflict resolution processes resolve the land dispute, preferring to use the method of advocacy through litigation and non litigation. Until now the process of advocacy as the choice of conflict resolution have not been able to resolve the conflict even more protracted conflict and lead to acts of violence whether committed by farmers Toili and PT KLS. This study uses the method of evaluation that is part of the decision making process, namely to compare an event, activity has been determined. This study uses qualitative analysis and data types. Qualitative research aims to describe and analyze problems that become the object of this study as an evaluation of the advocacy process, so this study can give an idea about advocacy in conflict resolution of land disputes and the factors surrounding the advocacy process to determine the success or failure of advocacy efforts related to resolving conflicts and land disputes Toili farmers PT KLS.